2005
DOI: 10.1073/pnas.0506803102
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor (TLR) polymorphisms in African children: CommonTLR-4variants predispose to severe malaria

Abstract: Genetic host factors play a substantial role in susceptibility to and severity of malaria, which continues to cause at least one million deaths per year. Recently, members of the toll-like receptor (TLR) family have been shown to be involved in recognition of the etiologic organism Plasmodium falciparum: The glycosylphosphatidylinositol anchor induces signaling in host cells via TLR-2 and -4, whereas hemozoin-induced immune activation involves TLR-9. Binding of microbial ligands to the respective TLRs triggers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
214
7
16

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(257 citation statements)
references
References 62 publications
20
214
7
16
Order By: Relevance
“…Significant differences in allele frequencies have been reported between ethnically diverse populations. The TLR2 Arg753Gln polymorphism which is absent in our population, is similar to that observed in a case-control study among Ghanaian children (Mockenhaupt et al 2006). In European populations the frequency varies between 6-14% (Folwaczny et al 2004, Lorenz et al 2001.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Significant differences in allele frequencies have been reported between ethnically diverse populations. The TLR2 Arg753Gln polymorphism which is absent in our population, is similar to that observed in a case-control study among Ghanaian children (Mockenhaupt et al 2006). In European populations the frequency varies between 6-14% (Folwaczny et al 2004, Lorenz et al 2001.…”
Section: Discussionsupporting
confidence: 65%
“…A very low frequency of these polymorphisms was observed in our study population, 2.6% for Asp299Gly and 1.8% for Thr399Ile compared with similar studies in Spanish and German populations (Schroder et al 2003, Sánchez et al 2004). These polymorphisms have been observed associated with severe malaria (Mockenhaupt et al 2006) and Gram-negative infection (Genc et al 2004). In T. cruzi infection, both in vitro and knockout mice studies, have shown that innate immunity plays a crucial role in resistance to infection, as well as in parasite-induced cytokine response, TLR4-mutant mice were susceptible to T. cruzi infection with higher parasitemia showing earlier mortality , Oliveira et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gram-negative infection 31 or septic shock due to Gram-negative organisms, 32 severe malaria, 33 brucellosis, 34 Crohn's disease 35 and severe sepsis following burn injury. 36 On the other hand, the same alleles have shown protective effects against various diseases such as atherosclerosis, 37 Legionnaire's disease 38 and late-onset Alzheimer's disease.…”
Section: Discussionmentioning
confidence: 99%
“…SNP Asp299Gly was later shown to co-segregate with SNP Thr399Ile-also in the third exon of TLR4. Both SNPs are present in 10% of Caucasian populations and are reported to have a positive correlation with susceptibility to several infectious diseases (including gram-negative sepsis), atherosclerosis, asthma, malaria and also Helicobacter pylori-induced gastric cancer and its precursors (Mockenhaupt et al, 2006;Hold et al, 2007). However, neither SNP is present in Asian populations.…”
Section: Toll-like Receptormentioning
confidence: 99%